Aplicação do software ScicosLab/Scilab no controle automático de geração de sistemas de potência explorando o problema de despacho econômico - Almeida Junior, Deoclides Alves de (2012)
The purpose of this paper is to show that ScicosLab/Scilab software can be used as an interesting and effective computational tool to analyze the automatic generation control of an electric power system for the old vertical structure as well as for the current unregulated version where the economic dispatch analysis is of fundamental importance. Firstly it is presented the software and, afterwards, the concepts and definitions of rotational movements in order to develop mathematical models for the generators equipped with steam turbines or hydraulic turbines and speed governors, and for their electrical loads. For the studies it is used a system comprised by two distinct interconnected areas where a load increase in one area is simulated without/with the tieline, ignoring, and then considering the primary and supplementary controls. Finally, it is analyzed a more realistic system with three distinct areas extracted from the Brazilian power system. The computational results show graphically the variations of the two main quantities of interest: the frequency of each area of the system and the tieline power. These quantities allow the evaluation of the system behavior after a disturbance that affects the generation-load balance. Within the above context, it is verified that the ScicosLab/Scilab computer package effectively models and simulates the load-frequency control of a power system, including the economic aspects, qualifying, therefore, as an excellent alternative to replace any similar program that requires license payment.